Microgrid System Evaluation Using Capacity Factor For an Off-grid Community in Nigeria - Amuta, Elizabeth Oses; Tita, Wara Samuel; Felix, Agbetuyi Ayoade; Evwieroghene, Orovwode Hope; Simeon, Matthew; Somefun, Tobi (International Journal of Energy Economics and Policy, 2022)
With the high rate of economic development, there is an increasing load demand even in rural communities and Obayantor in Nigeria. Obayantor, having zero connection to the primary grid, needs electricity. Following the community located in a tropical rejoin of Nigeria, it has enough solar energy sources. With the high price of diesel fuel, solar microgrid seems to be the best energy solution for the rural community. In this study, technical and economic analysis was carried out on the solar-based microgrid and compared with a diesel-only microgrid using MATLAB Software tool. The results show that the solar microgrid is more cost-effective and has a cheaper COE, affordable for the rural community compared with the diesel microgrid, which is more expensive to afford. The Annual system cost for the solar microgrid was lower compared with the diesel source. The result also revealed that the diesel-alone microgrid system is 4.71 times and 0.2 times more costly than the solar-based microgrid system in terms of the cost of energy and ASC, respectively. Thereby making the diesel microgrid not having technical and economic feasibility for the community.